Does paradoxical leadership influence employees’ proactive work behavior? A study based on employees in Chinese state-owned enterprises - Qiang, Qin; Xiaohong, Wu; Qianru, Song (Frontiers in Psychology, 2023)
Paradoxical leadership has emerged as an increasingly important research topic in the context of Chinese state-owned enterprises, which are currently facing contradictions between maintaining stability and implementing changes, short-term profits and long-term sustainable development, and public nature and marketization. Based on social cognitive theory and social exchange theory, this study employed a questionnaire survey to explore the influence of paradoxical leadership on employees’ proactive work behavior and the mediating role of superior-subordinate guanxi and self-efficacy. The study involved 540 employees working in Chinese state-owned enterprises. We conducted confirmatory factor analyses to test the validity of the measurement model and regression to evaluate the direct effects. Subsequently, we used bootstrapping to confirm mediation and serial mediation effects. The study found that (1) Paradoxical leadership can effectively enhance employees' proactive work behavior; (2) The superior-subordinate guanxi plays a mediating role between paradoxical leadership and employees' proactive work behavior, that is, paradoxical leadership enhances employees' proactive work behavior by improving the superior-subordinate guanxi; (3) Self-efficacy plays a mediating role between paradoxical leadership and employees' proactive work behaviors, that is, paradoxical leadership promotes employees' proactive work behavior by enhancing their self-efficacy; (4) The superior-subordinate guanxi and self-efficacy play a chain mediating effect between paradoxical leadership and employees' proactive work behavior, forming a chain of "Paradoxical leadership -- Superior-subordinate Guanxi -- Self-efficacy -- Employees' proactive work behaviors". This study enriches the theoretical research on paradoxical leadership and provides suggestions for state-owned enterprises to enhance employees' proactive work behavior.